PENGARUH INDIKATOR PERUBAHAN IKLIM TERHADAP PENDAPATAN PETANI PADI SAWAH DI KELURAHAN LAMATTI RILAU - Zahwa, Nabila Amara; Megawati, Megawati; Nurdin, Fadilah (Lembaga Penelitian, Pengembangan, Pemberdayaan Potensi Indonesia, 2025)
This study aims to determine the impact of climate change on the income of lowland rice farmers in Lamatti Rilau Village. The research method used is quantitative with a cross-sectional study approach. This study was conducted in Lamatti Rilau Village, North Sinjai District, in June 2025. Data collection techniques were based on observation and questionnaires. The population in this study consisted of 381 members of farmer groups in Lamatti Rilau Village in 2024, while the sample size was calculated using the Slovin formula, resulting in 79 respondents. The sampling technique used was simple random sampling. The results of the study indicate that the adjusted R square value is 0.349 or 34.9%, which means that the independent variables jointly or simultaneously influence the dependent variable by 34.9%. Meanwhile, 65.1% of the income of lowland rice farmers is influenced by other variables not included in this study. The conclusion is that, partially, the shift in planting season and plant pest organisms (OPT) have a significant impact on the income of lowland rice farmers in Lamatti Rilau Village, while the decrease in production has an insignificant impact on their income. Simultaneously, there is a significant impact of the shift in planting season, decreased production, and plant pest organisms (OPT) on the income of lowland rice farmers in Lamatti Rilau Village